If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 24 = 13x + -57 Reorder the terms: 24 + 4x = 13x + -57 Reorder the terms: 24 + 4x = -57 + 13x Solving 24 + 4x = -57 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 24 + 4x + -13x = -57 + 13x + -13x Combine like terms: 4x + -13x = -9x 24 + -9x = -57 + 13x + -13x Combine like terms: 13x + -13x = 0 24 + -9x = -57 + 0 24 + -9x = -57 Add '-24' to each side of the equation. 24 + -24 + -9x = -57 + -24 Combine like terms: 24 + -24 = 0 0 + -9x = -57 + -24 -9x = -57 + -24 Combine like terms: -57 + -24 = -81 -9x = -81 Divide each side by '-9'. x = 9 Simplifying x = 9
| 9x-39=3x+3 | | 6x+43=9x+13 | | -7m+46-6(m-5)=9m-(8m-3)-3m+7 | | 11x+7=9x+17 | | -7(x+6)=2x+12 | | -12p-4(3-5p)=3(p-3)-28 | | 25-4x=5x+15 | | 5-10x=41-17x | | 0.4x-8=20+0.75x | | -101-8x=9x+18 | | 4x+7=-92-7x | | 8x-4(-5x-2)=12x | | 159-5x=5x+19 | | 6x-10-3x=7x-5 | | 42x-13=42 | | -11-6x=7-9x | | 15(n+9)=3(45+5n) | | 70-3x=8x+15 | | 6x-10x+14=-2x+6 | | 3-6p-2=13 | | 2x+9=37-2x | | 6x+84=12x+12 | | -12=-6a-6a | | 4x-8+3x+27=28 | | 8x+8=6x+16 | | 4(2x-4)=7x+2 | | 4(x+9)+2=38 | | 2(x-2)+16=5x-9 | | 6y-2=-15+y | | 9x-30=60 | | m+(-96)=-55 | | 227-2x=43x+17 |